The effects of foreign direct investment on labour productivity - Носова, О. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The study of the effects of foreign direct investment (FDI) on the productivity of local firms is aimed at estimating its potential impact in terms of its strengthening activity in developing countries. The article seeks to examine the effects of FDI on labour productivity of local firms and determine the factors that would facilitate the development of more efficient policy to attract FDI to Ukraine. The actual relationship between horizontal and vertical side effects of FDI remains unclear, although the available studies revealed some positive correlations. While recent studies highlight the considerable research efforts made to understand the issues of the investment motivation of the FDI, its impact on economic growth and competitive advantages in developed economies. Empirical studies of FDI effects on domestic firms expose various factors, conditions and characteristics at the national, industry and firm levels. The reported results do not reflect the ambiguous effects of economic sectors on labour productivity, undervalued labour costs per worker, and do not take into account the role of the shadow economy in Central and Eastern European countries. Inadequate skills and education of workers are estimated to be a major or severe obstacle for the operation of multinational companies in many developing countries. The government policy on liberalization of FDI inflows makes local markets more attractive for foreign companies. Government support for education and training is a key factor in attracting FDI. The gains achieved from FDI have prompted the government to encourage FDI inflows. The paper discusses the challenges faced by the government to promote policies for attracting FDI in developing countries.